What Happened to Franklin Square Park? People, Trees, and Environmental Justice. Issue 1 (2nd January 2021) - Brown, Milan; Shcheglovitova, Mariya
Abstract : Based in Baltimore, Maryland, this project employs methods from urban forestry and community-engaged research to gain a deeper understanding of a city park's physical quality and the meaning of park quality to neighborhood residents. In the summer of 2018, we were asked by residents living in the Franklin Square community to survey the trees in their neighborhood park and create an updated park map. Following the completion of our survey, we organized an event in the park for local elementary and middle school students and collected student reflections on the park before and after the event. Despite indications that the physical quality of the park is deteriorating through the loss of trees and other park features, our qualitative analysis of themes from student reflections and historical narratives suggests that not only park features but also experience, memory, and history shape park quality. By examining green space quality using a bottom-up approach, which includes the voices of community members and archival documents, we advance and question studies of urban green space quality that have largely relied on quantitative metrics.